Analyzing the drivers of smart sustainable circular supply chain for sustainable development goals through stakeholder theory - Kayikci, Yasanur; Kazancoglu, Yigit; Gozacan‐Chase, Nazlican; Lafci, Cisem (Business strategy and the environment, 2022)
The concept of sustainable development is becoming incomprehensible and complex in global supply networks, especially in low‐ and middle‐income countries (LMIC) that are most affected by ever‐changing industry challenges and standards. Smart technologies emerged by Industry 4.0, sustainability, and circular economy (CE) connection, which remain unexplored, can be integrated into the supply chain as a business strategy to increase collaboration and cooperation between different tiers of the supply chain to achieve sustainable development goals (SDGs) according to LMIC. Therefore, the main objective of this paper is to discover the drivers of a smart sustainable circular supply chain (SSCSC) in achieving the SDGs in LMIC through stakeholder theory. First, a systematic review is employed to identify the drivers of the SSCSC to achieve the SDGs in the LMIC incorporating existing literature on the subject. Second, the Best‐Worst Method (BWM) is applied to analyze the identified drivers, and then the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) is used to analyze the SDGs. The applicability of the solution methodology was illustrated by providing a numerical example. The results of the study are twofold: firstly, drivers are analyzed by implementation of BWM. The results of the BWM reveal that economic sustainability is the best key driver among the eight driversin achieving the SDGs, meaning that without financial assistance and support achieving the SDGs becomes ineffective. Secondly, the TOPSIS analysis reveals that SDG 16 (peace, justice, and strong institutions) is the SDG most supported by drivers.